Human Capital dan Produktivitas Tenaga Kerja: Studi Empiris pada Pekerja Formal dan Informal di Kota Padang - Fiko Farlis; Tri Rachmat Riski; Jolianis .; Afdhal Cassady Heru (CV. ITTC INDONESIA, 2026)
Labor productivity is an important indicator in supporting economic growth and regional competitiveness. However, the dominance of the informal sector in Indonesia’s labor market is often associated with lower productivity due to limited access to education, training, and employment protection. This study aims to analyze the effect of human capital on labor productivity among formal and informal workers in Padang City. This study employed a quantitative approach with a cross-sectional design involving 384 labor respondents selected using proportionate stratified random sampling. Data were analyzed using multiple linear regression with robust standard errors through STATA software. The variables examined included labor productivity, employment status, education, work experience, age, and gender. The findings indicate that formal and informal employment status does not significantly affect labor productivity. Education has a positive and significant effect on productivity, while gender has a significant negative effect. Work experience and age show marginal effects on labor productivity. Labor productivity in Padang City is more strongly influenced by the quality of human capital than by employment formality. Therefore, improving education, job training, and workforce competency development should become the primary focus of labor productivity enhancement policies in both formal and informal sectors.